Identifikasi Letak Dan Bentuk Sorus Pada Paku (Pterydophyta) Dikawasan Universitas Bengkulu - Reta Pramala Utami (Pandawa Institute, 2023)
Sorus is a collection of complex sporangiums in which there are spores. Found on the upper (Addaksial) and lower (Abaksial) surfaces of the leaves of spike plants (Pteridophyta). This activity aims to identify the location and shape of the sorus on the nails in the Bengkulu University area. Sampling using purposive sampling methods. The identification results found differences in the location and shape of the sorus from the spike plant (Pterydophytha) in the Bengkulu University area. There are 9 families of spike plants (Pterydophytha) identified, namely Lygodiaceae, Gleicheniaceae, Dryopteridaceae, Cyatheaceae, Pteridaceae, Lomariopsidaceae, Osmundiaceae, Aspleniaceae, Polypodiaceae. The location of the spike plant sorus is at the end of the stem between the leaf bones, the veins of the leaf, near the edge of the leaf and on the edge of the leaf. The shape of the sorus of the spike plant (Pterydophytha) there are three, namely round, elongated and.